Digital Friends and Empathy Blindness - Bangsgaard Alberte Romme; Kløve Ryelund Cecilia; Lind Nilsson Mathilde Marie; Søgaard Anders (Open Philosophy)
Can chatbot-based virtual relationships replace physical ones? One possible bottleneck is lack of empathy in chatbots, as well as the attraction of physical relationships. Through a mixture of survey and respondent interviews, we investigate perceived chatbot empathy with devoted users, as well as how virtual relationships have affected their physical relationships. We found that Replika users experience high levels of empathy in their interactions with the chatbot, and that extensive use leads to (reported) reduced interest in physical relationships. We speculate whether extensive use of social chatbots can lead to empathy blindness and apathy over time.